Individualized and Innovation-Centered General Education in a Chinese STEM University - Xu Li; Yuan Li (MDPI AG, 2023)
The concept and practice of general education have been widely discussed and debated in the Euro-American world, but its adaptation in China needs further discussion and understanding. Over the past decade, its impact on Chinese higher education is increasingly salient, with a large number of Chinese first-tier universities claiming to initiate general education reforms to their previously narrowly focused undergraduate programs. This paper explores the development, implementation, and support of general education in a new type of research university in China from an organizational perspective. Through a case study of the Southern University of Science and Technology (SUSTech) prior to the COVID-19 pandemic, this paper examines SUSTech's individualized and innovation-based general education system, highlighting its institution-wide approach and innovation-centered perspective. The findings underscore the importance of integrating general education principles throughout the university to foster self-directed thinkers and cultivate students' self-awareness, interests, and passions. This study also reveals how general education is used as an organizational solution to address a variety of historical and complicated issues that challenge Chinese universities. This research serves as a catalyst for reform and innovation in Chinese higher education, inspiring transformative practices that meet the evolving needs of students and society.